Uncertainty Quantification in Scientific Computing 10th IFIP WG 2.5 Working Conference, WoCoUQ 2011, Boulder, CO, USA, August 1-4, 2011, Revised Selected Papers - Dienstfrey, Andrew M.; Boisvert, Ronald F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed post-proceedings of the 10th IFIP WG 2.5 Working Conference on Uncertainty Quantification in Scientific Computing, WoCoUQ 2011, held in Boulder, CO, USA, in August 2011. The 24 revised papers were carefully reviewed and selected from numerous submissions. They are organized in the following topical sections: UQ need: risk, policy, and decision making, UQ theory, UQ tools, UQ practice, and hot topics. The papers are followed by the records of the discussions between the participants and the speaker.
UQ Need: Risk, Policy, and Decision Making -- UQ Theory -- UQ Tools -- UQ Practice -- Hot Topics. .
Keywords: Computer science; Software engineering; Electronic data processing; Computer simulation; Information systems; Computer Science; Computation by Abstract Devices; Simulation and Modeling; Software Engineering; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; Numeric Computing